Clinical assessment of ethinylestradiol and cyproterone acetate in menstrual irregularities of hyper-androgenic origin - Gama, Carlos Romualdo Barbosa [UNESP]; Gama, Gustavo Falcão; Lasmar, Ricardo Basil; Fonseca, Rogerio Sergio; Guimarães, Lucia Cunegatto; De Aquino, Sabrina; Geller, Mauro; Ribeiro, Rachel Leite (My University, 2010)
We report on the results of a double-blind, randomized, controlled clinical trial comparing two preparations of ethinylestradiol and cyproterone acetate in the treatment of women of reproductive age presenting menstrual irregularities of hyper-androgenic origin. After obtaining informed consent, subjects were randomized to a 4-month treatment period consisting of one daily dose of 0.035mg ethinylestradiol + 2mg cyproterone acetate. The treatment regimen cycle consisted of one pill, once daily for 21 days, followed by a 7-day pill-free period. We compared the efficacy of two presentations of the drug combination after each treatment cycle (Visits 2, 3, 4, and 5) in establishment and maintenance of menstrual regulation, intensity of menstrual flow, and dysmenorrhea, as well as a comparison of the two presentations in terms of Global Satisfaction and Drug Satisfaction assessments performed by the patients and the investigating physician. At each study visit, drug compliance and use of concomitant medications, as well as incidence, severity and duration of adverse events were recorded. A total of 86 subjects were randomized to treatment, with 43 subjects in each treatment group. At Visit 2 and each subsequent visit, all patients in both treatment groups reported an episode of withdrawal bleeding during the 7-day hormone-free period. We observed a statistically significant (p<0.0001) decrease in the incidence of dysmenorrhea at each study visit in relation to the pretreatment assessment. There was a significant reduction (p<0.0001) in the number of subjects reporting intermenstrual bleeding at each study visit in both treatment groups. Global Satisfaction scores by the patient and physician increased significantly at each successive study visit in both treatment groups. There were no clinically significant changes in vital signs, weight, and body mass index throughout the study period in either group. The number of subjects reporting adverse events at each visit did not vary between treatment groups. The combined oral contraceptive pill containing ethinylestradiol and cyproterone acetate was found to be both effective and safe in the menstrual irregularities of hyper-androgenic origin (amenorrhea, dysmenorrhea, and intermenstrual bleeding) assessed in this study. © Copyright Moreira Jr. Editora. Todos os direitos reservados.
Keywords: Cyproterone acetate; Ethinylestradiol; Hyperandrogenism; Menstrual irregularity; cyproterone acetate; ethinylestradiol; oral contraceptive agent; abdominal erythema; adult; amenorrhea; asthenia; body mass; breakthrough bleeding; breast tenderness; chloasma; clinical trial; controlled clinical trial; controlled study; double blind procedure; drug efficacy; drug induced headache; drug safety; drug synthesis; dysmenorrhea; erythema; female; gastrointestinal symptom; glucose blood level; human; leg edema; libido; major clinical study; menstrual cycle; menstrual irregularity; menstruation; mood change; patient compliance; patient satisfaction; pelvic erythema; randomized controlled trial; side effect; sleep disorder; vital sign; withdrawal bleeding